Perancangan Logo Dan Desain Kemasan MOGU Cookies Sebagai Identitas Visual - Subudiartha, I Nyoman; Satria, Christofer; Hasbullah, Hasbullah (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2024)
Logos and packaging are very important to face competition in the culinary business world today, where logos are company identities and packaging is a tool to protect products from various risks of damage, as a promotional tool which supports product sales and packaging is also very influential. in implanting the product in the minds of consumers, so that it can attract consumers. Therefore, this design was carried out to create a logo and packaging design for Mogu Cookies because previously this MSME did not have a logo and packaging design. The aim of this design is to provide a visual identity or logo and packaging design to improve the product image and the uniqueness of this product. This design was carried out using the design thinking method (empathize, define, ideate, prototype. Test) as well as carrying out appropriate 5W1H and SWOT analyzes to conduct interviews and find out more and in detail about the product being studied. The result of this design is a new design to create a logo and design for primary, secondary and packaging displays in order to improve and introduce this product.